Role of echocardiography in the evaluation of syncope: a prospective study. Issue 4 (1st October 2002) - Sarasin, F P; Junod, A-F; Carballo, D; Slama, S; Unger, P-F; Louis-Simonet, M
Abstract : Objective: To study the role of echocardiography in the stepwise evaluation of syncope. Design: A prospective observational study with an 18 month follow up. Setting: University teaching hospital providing primary and tertiary care. Subjects: 650 consecutive patients with syncope and clinical suspicion of an obstructive valvar lesion, or with syncope not explained by history, physical examination, or a 12 lead ECG, who underwent bidimensional Doppler transthoracic echocardiography. Main outcome measures: The causes of syncope were assigned using published diagnostic criteria. Echocardiography was considered diagnostic when confirming a suspected diagnosis, or when revealing occult cardiac disease explaining the syncope. Results: A systolic murmur was identified in 61 of the 650 patients (9%). Severe aortic stenosis was suspected in 20 of these and was confirmed by echocardiography in eight. Follow up excluded further cases of aortic stenosis. In patients with unexplained syncope (n = 155), routine echocardiography showed no abnormalities that established the cause of the syncope. Echocardiography was normal or non-relevant in all patients with a negative cardiac history and a normal ECG (n = 67). In patients with a positive cardiac history or an abnormal ECG (n = 88), echocardiography showed systolic dysfunction (left ventricular ejection fraction ≤ 40%) in 24 (27%) and minor non-relevant findings in the remaining 64. Arrhythmias were diagnosed in 12 of the 24 patients with systolic dysfunction (50%), and in 12 of the 64 remaining patients (19%) (p < 0.01). Conclusions: Echocardiography was most useful for assessing the severity of the underlying cardiac disease and for risk stratification in patients with unexplained syncope but with a positive cardiac history or an abnormal ECG.